Simulasi Penempatan Rorak Sebagai Bentuk Pengoptimalan Konservasi Air - Akhmadi Puguh Raharjo (Jurnal ALAMI : Jurnal Teknologi Reduksi Risiko Bencana, 2020)
Trenching is a form of soil and water conservation engineering that is commonly used and is known to be effective in controlling runoff and increasing water content in the root zone of plants. There are various configurations of trench placement in the field and this study aims to simulate the placement of trench by comparing the three trench configurations to find out which configuration is most effective in capturing surface runoff. The simulation is carried out by calculating the catchment capacity of surface runoff under different rainfall intensity conditions and runoff coefficients in the three trench configurations that have different catchment areas. From the calculation, it is known that configuration 3 in optimal conditions has a comparative advantage of 41.67% - 68.80% (compared to configuration 1) and 27.78% - 52.83% (compared to configuration 2). Meanwhile, configuration 2 has a comparative advantage of 13.89% - 16.06% when compared to configuration 1. From the calculation it is also known that there are conditions where the three configurations will produce a uniform value so that there will be no comparative advantage between the three configurations. This condition is generally above the rain intensity of 50 mm per hour and the runoff coefficient is above 0.45.